Harmonics in Offshore Wind Power Plants Application of Power Electronic Devices in Transmission Systems - Glasdam, Jakob Bærholm (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2016)
This book reports on cutting-edge findings regarding harmonic stability assessment for offshore wind power plants (OWPPs). It presents a timely investigation of the harmonic stability interaction between OWPPs on the one hand, and associated control systems in the wind turbines and other power electronic devices in the transmission system on the other. The book particularly focuses on voltage-sourced converter high-voltage direct current (VSC-HVDC) and static compensator (STATCOM) systems. From a practical perspective, the book reports on appropriate models for power electronic devices. It describes how the frequency domain evaluation approach can be assessed by comparing results obtained with the Nyquist stability criterion against the more detailed electromagnetic transient based model realized in the PSCAD/EMTDC simulation program. The book also provides a concise yet complete overview of large OWPPs that incorporate power electronic devices on a broad scale, and highlights selected challenges and opportunities in the context of real-world applications.